Konsep Kepemimpinan Raden Mas Sahid Dan Aplikasinya Di Zaman Modern - Bani Sudardi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The prince of Mas Sahid or Mangkunegara I is a figure who has an extraordinary leadership spirit so as to be able to establish mangkunegaran work with a strong army. The paper of this study seeks to understand the concept of mangkunegaran. The paper of this study used literature review method. The emergence of mangkunegaran legions comes from the struggle of The prince of Mas Said along with his followers who feel disillusioned with the government and then injustice done by Paku Buwono II. The embryos of the mangkunegaran legion are soldiers eho fought together with The prince of Mas Said. With “ikrar tiji tibeh” which means if one of the fallen all feel, when one gets happiness then all participate in enjoying it, the way it the purpose of The prince of Mas Said to unite his legions and getting win in the warious battles. In his struggle, The prince Mas Said cooperates with Sunan Kuning and the prince of Mangkubumi. When working with Sunan Kuning, The prince of Mas Sahid is equipped with the ability to set strategies and how to use weapons and then then appointed as a “senopati” with the title of prince of prangwedanan who led 300 death squads of soldiers. The first battle with Sunan Kuning was against the soldiers of Kompeni and soldiers of Ternate and then the prince of Mas Said is winner. After conquering Madiun and Ponorogo, the prince of Mas Said dissever with Sunan Kuning, the prince of Mas Said was later caught and wxiled to Sri Langka. The paper is attempts to reveal the concept of leadership of the prince of Mas Said that managed to win various wars and then united the troops.